Ketidaksantunan Interaksi Jual Beli Akun Maz Aruel di TikTok: Analisis Siber Pragmatik Perspektif Jonathan Culpeper - Aldi Firnanda; Agus Purnomo Ahmad Putikadyanto; Iswah Adriana; Mila Ayu Sri Wardani; Zainuri Ihsan (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This study examines the strategy of impoliteness in online buying and selling interactions of Madurese people using a cyber pragmatic approach. Impoliteness is a language behavior that violates the norms of politeness, causing feelings of discomfort, offense, and insult to the interlocutor. The purpose of this study is to analyze the form of impoliteness in online buying and selling interactions from Jonathan Culpeper's perspective. This study uses a qualitative descriptive method. Data were obtained through a non-participatory observation method of 100 TikTok videos of buying and selling interactions uploaded to the social media account